2013
DOI: 10.1093/mutage/ges075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic damage in patients with chronic kidney disease, peritoneal dialysis and haemodialysis: a comparative study

Abstract: Patients with chronic kidney disease (CKD) have signs of genomic instability and, as a consequence, extensive genetic damage, possibly due to accumulation of uraemic toxins, oxidative stress mediators and other endogenous substances with genotoxic properties. We explored factors associated with the presence and background levels of genetic damage in CKD. A cross-sectional study was performed in 91 CKD patients including pre-dialysis (CKD patients; n = 23) and patients undergoing peritoneal dialysis (PD; n = 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…This would explain the contradictory results observed in the literature when pre‐ and HD patients were compared. Thus, although higher values were reported in HD patients [Stopper et al, ; Stoyanova et al, ], the opposite has recently been observed [Rangel‐López et al, ] i.e. greater genomic damage was found in pre‐dialysis than in HD patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This would explain the contradictory results observed in the literature when pre‐ and HD patients were compared. Thus, although higher values were reported in HD patients [Stopper et al, ; Stoyanova et al, ], the opposite has recently been observed [Rangel‐López et al, ] i.e. greater genomic damage was found in pre‐dialysis than in HD patients.…”
Section: Discussionmentioning
confidence: 91%
“…The second problem is the low number of patients included in these studies (ranging from 12 to 141). The largest study was performed by our group [Stoyanova et al, ], and the next largest study included only 91 patients [Rangel‐López et al, ]. A description of all 12 studies is provided in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, time in hemodialysis was the only factor associated with increased levels of micronuclei in buccal cells, although this effect was not observed in patients submitted to peritoneal dialysis (Roth et al, ). Surprisingly, the contrary effects have been recently reported when peripheral blood lymphocytes were used (Rangel‐López et al, ). Perhaps this discrepancy can be attributed to sampling size more than to the targeted cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have on the one hand measured levels of genomic damage in both healthy volunteers and in HD patients [10] [21] [25] and, on the other, have determined levels of oxidative specific DNA disruption in patients with kidney disease [4], no previous work has used oxidative specific endonucleases (Endo III and FPG) to assess oxidative DNA damage simultaneously in HD patients and healthy controls. Even though the unmodified comet assay allows for the measure of overall alkaline DNA damage, the use of these two enzymes is most valuable as they recognise oxidative damage [18].…”
Section: Discussionmentioning
confidence: 99%